Pemanfaatan Panas di Pipa Tekanan Tingggi pada Mesin Pendingin (AC) - Aziz, Candra Yusfi Amri; Firdaus, Rahmat (Rekayasa Mesin, 2018)
The purpose of this research is to know the design of AC cooling machine system by using water cooling media in condenser, to know the influence of cooling water media on condenser to cooling machine performance (AC), to know COP cooling capacity based on the addition of water cooling media in condenser. The experiment was conducted by experimental method, which was used to test the temperature variation by analyzing air temperature (Th), water temperature (Tc), suction and discharge pressure, condenser inlet and outlet temperature, COP and cooling machine efficiency performed every 5 minutes once. The results showed, maximum temperature that can be achieved of cooling machine system is (4.4 oC) at minute 10 for cooling machine with air fan cooling medium (-6,9 oC) at minute 15 For cooling machine with water cooling medium (-12,7 oC) at minute 15 for cooling machine with water cooling medium and air fan. The flowing water flow affects the achievement of the best temperature and efficiency. In this experiment, the result of the mass of water flowing every minute is 0,4603 kg / s and able to stabilize hot calor to reach temperature (32 oC) which can be used for other needs.